Experimental study on helical tubes heat transfer characteristics considering corrosion products - Yulong, Mao; Shuqi, Meng; Xianghui, Lu; Desheng, Jin; Xiaoting, Wang; Kejia, Li; Yisong, Hu; Yousen, Hu; Min, Rui (Frontiers in Energy Research, 2023)
During the power operation of nuclear reactors, the corrosion products in the secondary circuit will deposit on the inside of Helical-coiled One-Through Steam Generator (H-OTSG) heat transfer tubes and form fouling. The main component of fouling is iron-based oxide, which generates from the heat exchangers made of cast iron. Fouling may change the local heat transfer characteristics of heat transfer tubes, and then affect the safety and economy of reactors. In order to obtain the distribution of fouling thickness and its action mechanism on helical tubes heat transfer characteristics, the heat transfer experiment under small pressurized reactors service environment was conducted. The experimental results indicate: corrosion products mainly deposit on onset of saturated boiling point with the maximum fouling thickness of 50μm, and induce local wall temperature elevating about 773K; fouling will increase the thermal equilibrium void fraction and hinder the heat transfer of helical tube, but has little impact on the onset position of saturated boiling point; corrosion products will release and re-deposit near dry-out point because of the flush of high speed vapor, causing the periodic fluctuation of thermal resistance of helical tube.